Particle packed columns and monolithic columns in high-performance liquid chromatography-comparison and critical appraisal - Unger, Klaus K.; Skudas, Romas; Schulte, Michael M. (Journal of Chromatography A, 2008)
The review highlights the fundamentals and the most prominent achievements in the field of high-performance liquid chromatography (HPLC) column development over a period of nearly 50 years. After a short introduction on the structure and function of HPLC columns, the first part treats the major steps and processes in the manufacture of a particle packed column: synthesis and control of particle morphology, sizing and size analysis, packing procedures and performance characterization. The next section is devoted to three subjects, which reflect the recent development and the main future directions of packed columns: minimum particle size of packing, totally porous vs. core/shell particles and column miniaturization. In the last section an analysis is given on an alternative to packed columns—monolithic columns, which have gained considerable attraction. The challenges are: improved packing design based on modeling and simulation for targeted applications, and enhanced robustness and reproducibility of monolithic columns. In the field of miniaturization, particularly in chip-based nano-LC systems, monoliths offer a great potential for the separation of complex mixtures e.g. in life science.